(untitled) (AL-FIKRAH: Jurnal Kajian Islam, 2025)
This study aims to examine the perspective of Islamic Law on the Ethics of the Advocate Profession and the efforts to defend suspected offenders in mitigating their sentences. The methodology employed is qualitative, focusing on library research supported by normative juridical and socio-historical approaches. The findings reveal several key points: First, the Ethics of the Advocate Profession are accommodated within Islamic values, including piety, honesty, justice, integrity, and professionalism, which are integral to Islamic teachings and reflected in the Indonesian Advocate Code of Ethics. Second, defending a suspect in a hudud case who has not yet appeared before a judge is permitted; however, once the case has reached the judge, such defense is prohibited. Nevertheless, if there is doubt or the suspect remains a mere suspect, an advocate may still provide defense. In the case of ta‘zīr crimes, defense for suspects and accused individuals is allowed. The implications of this research suggest that understanding Advocate Ethics from the perspective of Islamic Law can serve as a foundation for formulating just legal policies. Additionally, this study offers practical and academic contributions to government authorities, law enforcement agencies, society, and future researchers in exploring the relationship between positive law and sharia values within advocacy practices.